The Effect of Service Quality and Price on Client Loyalty Using The Services of Notary and PPAT Yousfrita in Jakarta - Dewa Putu Yohanes Agata L. Sandopart; Ramadhania, Dwi Nova; Budi, Budiman Abdulah; Sandopart, Dewa Ayu Indiana Ida L. (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of service quality and price on client loyalty at YOUSFRITA Notary and PPAT services, in Jakarta. This study uses survey, interview and questionnaire methods by collecting data through questionnaires to clients. The population in this study are clients who have used YOUSFRITA notary and PPAT services. Sampling size using the hair formula depending on the number of parameters in the form of question indicators in this study, namely, 30 multiplied by 5, so that 150 respondents were obtained. The collected data were analysed using descriptive statistical methods and testing of data collection instruments using the Partial Least Square (PLS) method. The results showed that there was a positive and significant effect of service quality and price variables on client loyalty. The practical implication of this research is the importance of companies focusing on improving service quality, setting competitive prices and paying attention to the overall customer experience. By implementing these strategies, YOUSFRITA notary and PPAT services, can build strong Client Loyalty and increase their competitive advantage in the market.